Perlindungan Keselamatan Kerja Anak Buah Kapal dalam Pelaksanaan Perjanjian Kerja Laut Perspektif Fatwa Majma’ Al-Fikih Islamiyy Ad-Dauli - Juwita, Gina; Tarigan, Tetty Marlina (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
Research on occupational safety and health protection for ship crew in the implementation of sea work agreements in Langkat district from the perspective of fatwa majma' al-fikih islamiyy ad-dauli, this study aims to find out how the implementation of occupational safety and health protection for ship crew if an accident occurs. accident at work. the research method used is empirical juridical, this research uses a type of field research (field research). The results of this study are due to the lack of legal awareness by the ship owner and crew in facilitating work equipment on board, there is also no written sea work agreement, the Sea Work Agreement that is owned as legal protection for the rights and obligations between the two sides party. A work agreement that is verbally not recorded in writing in the event of a dispute cannot provide legal protection.